2021
DOI: 10.1016/j.diabres.2021.108736
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the value of fasting plasma glucose in the first trimester for the prediction of adverse pregnancy outcomes

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 16 publications
(20 reference statements)
1
9
0
Order By: Relevance
“…Of note, the study excluded women with an FPG of more than 105 mg/dL (5.8 mmol/L) [ 33 ]. Several other studies have shown an association between LGA and macrosomia with elevation in first-trimester FPG [ 36 , 41 , 46 , 47 , 48 , 49 ]. A higher FPG was also associated with pregnancy-induced hypertension (PIH) [ 36 , 46 , 48 ], prematurity and preterm birth [ 46 , 48 ], non-evolutive pregnancies and fetal death [ 50 ], CS and assisted vaginal delivery [ 41 ], and neonatal intensive care unit (NICU) admission [ 51 ].…”
Section: Fasting Plasma Glucose For Diagnosis Of Egdmmentioning
confidence: 99%
See 4 more Smart Citations
“…Of note, the study excluded women with an FPG of more than 105 mg/dL (5.8 mmol/L) [ 33 ]. Several other studies have shown an association between LGA and macrosomia with elevation in first-trimester FPG [ 36 , 41 , 46 , 47 , 48 , 49 ]. A higher FPG was also associated with pregnancy-induced hypertension (PIH) [ 36 , 46 , 48 ], prematurity and preterm birth [ 46 , 48 ], non-evolutive pregnancies and fetal death [ 50 ], CS and assisted vaginal delivery [ 41 ], and neonatal intensive care unit (NICU) admission [ 51 ].…”
Section: Fasting Plasma Glucose For Diagnosis Of Egdmmentioning
confidence: 99%
“…Several other studies have shown an association between LGA and macrosomia with elevation in first-trimester FPG [ 36 , 41 , 46 , 47 , 48 , 49 ]. A higher FPG was also associated with pregnancy-induced hypertension (PIH) [ 36 , 46 , 48 ], prematurity and preterm birth [ 46 , 48 ], non-evolutive pregnancies and fetal death [ 50 ], CS and assisted vaginal delivery [ 41 ], and neonatal intensive care unit (NICU) admission [ 51 ]. An interesting observation was the higher risk of fetal complications arising from elevated FPG levels irrespective of subsequent GDM [ 48 , 51 ].…”
Section: Fasting Plasma Glucose For Diagnosis Of Egdmmentioning
confidence: 99%
See 3 more Smart Citations